Red blood cell distribution width as a predictor of outcome in Intensive Care Unit: a retrospective cohort study - Asmira Ljuca; Nermina Rizvanović; Senad Ljuca; Alma Jahić (Medicinski glasnik, 2023)
Aim: To evaluate the predictive significance of the red blood cell distribution width (RDW) >14.5 at admission to the Intensive Care Unit (ICU) on outcome parameters: length of hospital stay (LOHS), incidence of hospital mortality, 30-day mortality and 30-day survival after hospital discharge in unselected (surgical and non-surgical) critically ill patients. Methods: A total of 325 surgical and non-surgical critically ill patients were divided based on the RDW value at admission to the ICU into two groups: Group 1 (RDW >14.5) and Group 2 (RDW?14.5). Demographic and clinical parameters, laboratory findings, treatment and outcome parameters were compared between the groups. The predictive significance of RDW>14.5 on outcome parameters was analysed using linear regression analysis and univariate and multivariate logistic regression analysis, as appropriate. Results: In Group 1, LOHS was higher (19.77±15.15; p<0.000) as was the prevalence of hospital mortality (46.6%; p<0.0523), while 30-day survival after hospital discharge was lower (52.9%; p>0.026) compared to Group 2. RDW >14.5 was positively linearly related (r=0.64; r2=0.40; p=0.000) with LOHS. RDW >14.5 predicted the prevalence of in-hospital mortality with a 73.7% positive predictive value (AUC 0.62; sensitivity 70.1%; specificity 59.5%; p<0.05) and 30-day survival after hospital discharge with a 34.5% negative predictive value (AUC 0.45; sensitivity 58.3%; specificity 68.7%; p<0.05). Conclusions: RDW value >14.5 at admission to the ICU can predict prolonged hospital stay, higher mortality and lower survival rate. RDW >14.5 may be an inexpensive and widely available early warning to redirect diagnostic and therapeutic decisions and improve outcomes.
Keywords: critically ill patients; erythrocytes; logistic regression; survival rate